Pengaruh Siaran Langsung Dan Konten Promosi Terhadap Minat Beli Mahasiswa Bisnis Digital UPI Di TikTok Shop - -, Atthaya Layla Zhafira Hilwana; Adam Pratama Yudha Putra; Muhammad Fadhli Al Multazim; Muhammad Zhafran Hafiz; Syti Sarah Maesaroh (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
The increasingly intense business competition at the TikTok Shop makes sellers have to carry out promotional strategies that can attract consumers' buying interest in their products. Therefore, this study aims to find out how live broadcasts and promotional content influence the buying interest of UPI Digital Business students in the TikTok Shop. By using the associative quantitative research method, it can be seen how the relationship between live broadcast variables and promotional content variables as independent variables with buying interest as the dependent variable. From the total population, 33 UPI Digital Business students were sampled in this study based on the minimum sample size. The data collected through questionnaires were then analyzed using multiple regression analysis on SPSS version 27. Then from the results of the study, it was found that partially live broadcasts did not have a significant effect on purchase intention. Conversely, promotional content partially has a significant influence on buying interest and simultaneously, live broadcasts and promotional content can significantly influence UPI Digital Business students' buying interest in the TikTok Shop.